The Effect of Exercises in the use of Interactive Video in the Development of Learning Motivation and the Performance of Some Basic Skills for Free Swimming for Beginners - Hassanien Abdul-Wahid Abbas Shuaila (Journal of Global Pharma Technology, 2018)
The educational process is not simple, but it is a complex process and needs to make a lot of effort, which makes it face many challenges, perhaps the most obvious are the methods and tools used in the teaching of various subjects. In their work as swimmers for age groups, the researchers noted that the new players do not have the motivation to learn when performing skills and fear of access to water, which is reflected negatively on the level of learning and performance of these skills. The educational process is based on modern technologies to transfer information from teacher to learner, The learning process was done better, faster and with less effort, the preparation of exercises using interactive video in the development of learning motivation and the performance of some basic skills for free swimming for beginners. The aim of the research was to identify the effect of interactive video in the development of learning motivation and the performance of some basic skills in free swimming for beginners. The researchers used the two-group experimental approach to suit the nature of the study. The research community was identified by the Waves Swimming Academy in the province of Bebel (73), who's ages ranged from 12 to 16 years. The study sample was selected in a random way by (30) beginner and 41.09% of the research community. They were divided into two groups (experimental and control) for each group (15). The results reached the following conclusion: The development of learning motivation has a positive impact on learning some free swimming skills for beginners and that the special exercises have had a positive impact on the use of interactive video in teaching some basic skills of free swimming for beginners. Interactive video has a clear role in developing learning motivation and performing some basic skills for free swimming for beginners.Keywords: Exercises, Interactive video, Learning motivation and basic skills.